The English Teaching Activities Using Shift System During Pandemic At SMAN 3 Langsa: English Teaching Activities Using Shift System - Muslem Muslem; Shafrida Wati; Maulida Safira (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2022)
Abstract The aim of this research was to describe the experience of teaching activities using shift system during the pandemic and to know the obstacles students' experience in the learning activity. The method of this study was qualitative with descriptive design. Subject of the study was one teacher and 10 students of XI IPA3 of SMAN No.3 Langsa. The data were collected by using questionnaire and documentation. Based on the result of the research, the experience of teaching activity using shift system has an impact on the learning process. The teacher must arrange the schedule and students material according to the syllabus continuously for different days. It often leads the teacher to repeat the material was unintentionally. In addition, the duration of learning is only 30 minutes, which the previous was 45 minutes. Then, students also experienced obstacles during the learning. Students found difficulties in understanding the materials explained by the teacher because the duration was short. The system made them lazy to study as the learning is divided in to shift A & B. It can be concluded that the teaching activity using the shift system do not run optimally.